Generation and characterization of mecp2 mutant. - Aperador Redondo, Juan; Fernández Miñán, Ana María; Bogdanovic, Ozren (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*280.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.10123);" role="presentation">Motivation: <span dir="ltr" style="left: calc(var(–scale-factor)*105.90px); top: calc(var(–scale-factor)*280.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">Mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*136.80px); top: calc(var(–scale-factor)*280.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04759);" role="presentation">gene encodes the Methyl CpG binding protein (MeCP2). This protein is known for being an important <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*292.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07266);" role="presentation">regulator of gene expression that interacts with methylated and unmethylated genomic DNA regions, and enhances or <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*304.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02119);" role="presentation">silences transcriptional processes. Different mutations of the MeCP2 protein in humans can lead to a variety of symptoms in <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*316.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02882);" role="presentation">Rett syndrome (RTT), a rare disease which causes abnormalities during female brain development as well as acute mental <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*328.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04367);" role="presentation">and physical disability. These misfunctions are caused by mutations in one or two of the domains that can be found in the <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*340.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02657);" role="presentation">MeCP2 protein: the methyl binding domain (MBD) and the transcriptional repression domain (TRD). The aim of this study is <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*352.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02342);" role="presentation">the generation of a knock-out (KO) mutant of the <span dir="ltr" style="left: calc(var(–scale-factor)*255.60px); top: calc(var(–scale-factor)*352.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*285.70px); top: calc(var(–scale-factor)*352.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01708);" role="presentation">gene in zebrafish by employing the CRISPR/Cas9 technique. Once <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*364.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02841);" role="presentation">we obtain the homozygous mutant, we will elucidate the significance of this mutation by deep RNA sequencing (RNA-Seq), <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*376.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0049);" role="presentation">focusing on the differences between transcripts present in wild type (WT) and homozygous mutant fish. These results will give <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*388.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05044);" role="presentation">us an indication of which genes are potentially regulated by the MeCP2 protein, which could render zebrafish as a useful <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*400.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00052);" role="presentation">model system aimed at understanding RTT etiology <span dir="ltr" style="left: calc(var(–scale-factor)*262.30px); top: calc(var(–scale-factor)*400.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998502);" role="presentation">in vivo. <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07908);" role="presentation">Methods: <span dir="ltr" style="left: calc(var(–scale-factor)*96.59px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0175);" role="presentation">To create the <span dir="ltr" style="left: calc(var(–scale-factor)*152.20px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*181.70px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999283);" role="presentation">KO, we designed sgRNA guides targeting the <span dir="ltr" style="left: calc(var(–scale-factor)*365.40px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*394.89px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998528);" role="presentation">exon 2, using the <span dir="ltr" style="left: calc(var(–scale-factor)*466.00px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999378);" role="presentation">CRISPRscan <span dir="ltr" style="left: calc(var(–scale-factor)*521.49px); top: calc(var(–scale-factor)*424.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998632);" role="presentation">software. <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*436.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04379);" role="presentation">We then tested the sgRNAs in F0 by microinjection of single-cell stage zebra-fish embryos. The embryos were allowed to <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*448.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03394);" role="presentation">develop to 24-48 hours post fertilization (hpf), after which they were genotyped. Amplification of regions of interest by PCR <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*460.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00184);" role="presentation">followed by electrophoresis in agarose gel, showed us that the sgRNAs worked, as we could see a band different to that of the <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*472.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03787);" role="presentation">WT (471bp). After the raising of the F0, we genotyped the mutant individually to identify founders. The founders of interest <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02028);" role="presentation">were named as follows: (i) <span dir="ltr" style="left: calc(var(–scale-factor)*164.10px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01393);" role="presentation">mecp2 26⚦<span dir="ltr" style="left: calc(var(–scale-factor)*211.70px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0273);" role="presentation">, with a deletion of 181bp, (ii) <span dir="ltr" style="left: calc(var(–scale-factor)*333.30px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01393);" role="presentation">mecp2 27 ,⚦ <span dir="ltr" style="left: calc(var(–scale-factor)*386.50px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02239);" role="presentation">with deletion of 15bp and (iii) <span dir="ltr" style="left: calc(var(–scale-factor)*507.00px); top: calc(var(–scale-factor)*484.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01393);" role="presentation">mecp2 13 ,⚦ <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*496.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02808);" role="presentation">with a deletion of 8bp. These founders were out-crossed with WT zebra-fish to stabilize the mutation (F1), and the offspring <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*508.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00355);" role="presentation">was genotyped and raised. We then genotyped the F1 generation by extracting the DNA from fin tissue (fin-clip); i<span dir="ltr" style="left: calc(var(–scale-factor)*507.40px); top: calc(var(–scale-factor)*508.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00237);" role="presentation">t is expected <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*520.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02675);" role="presentation">that 25% of this generation should be heterozygous. Once we have sequenced the heterozygous candidates for the <span dir="ltr" style="left: calc(var(–scale-factor)*530.20px); top: calc(var(–scale-factor)*520.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*532.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07328);" role="presentation">gene, we will in-cross a male and a female with the same mutation, in order to have a homozygous F2. Finally, we will <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*544.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04416);" role="presentation">genotype the F2 individually at 72h, extracting the DNA and RNA at the same time, using the <span dir="ltr" style="left: calc(var(–scale-factor)*444.40px); top: calc(var(–scale-factor)*544.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02771);" role="presentation">qiagen DNAeasy blood and <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*556.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998767);" role="presentation">tissue <span dir="ltr" style="left: calc(var(–scale-factor)*80.09px); top: calc(var(–scale-factor)*556.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998657);" role="presentation">kit for DNA and <span dir="ltr" style="left: calc(var(–scale-factor)*143.70px); top: calc(var(–scale-factor)*556.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01453);" role="presentation">Trizol <span dir="ltr" style="left: calc(var(–scale-factor)*168.20px); top: calc(var(–scale-factor)*556.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999257);" role="presentation">for RNA. The RNA of the confirmed homozygous mutants will be sent for RNA-Seq analysis. <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*580.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.10811);" role="presentation">Results and conclusions: <span dir="ltr" style="left: calc(var(–scale-factor)*167.89px); top: calc(var(–scale-factor)*580.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01741);" role="presentation">We have generated heterozygous <span dir="ltr" style="left: calc(var(–scale-factor)*308.60px); top: calc(var(–scale-factor)*580.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999445);" role="presentation">mecp2 <span dir="ltr" style="left: calc(var(–scale-factor)*338.90px); top: calc(var(–scale-factor)*580.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02701);" role="presentation">mutants, that we have to genotype, from the founders <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*592.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02024);" role="presentation">mentioned above (F1). The deletions sequenced cause the generation of a stop codon, so the MeCP2 protein should not be <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*604.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01918);" role="presentation">expressed in homozygous fish. The next step will be generating the homozygous generation in order to study the phenotype <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*616.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00139);" role="presentation">and perform the RNA-Seq at 72h of embryo development. Once we obtain the results of the RNA-seq analysis, we will be able <span dir="ltr" style="left: calc(var(–scale-factor)*54.10px); top: calc(var(–scale-factor)*628.67px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00202);" role="presentation">to explain which are the genes whose expression is modulated by MeCP2 and that are potentially implicated in RTT